Photo-catalytic Water Remediation Using Mixed Metal-organic Frameworks - Sumangaladevi, Sreevidya Mohanachandran; Pavithran, Rani; Usha, Nisha Krishnan (Current Catalysis, 2025)
IntroductionThe breakdown of organic contaminants from wastewater can be facilitated by metal-organic frameworks, which are three-dimensional coordination polymers with a large number of active sites and an organised porosity architecture.MethodsUsing Zn, Cu, Mn, Cd, and Cr metal salts together with 1,4-benzenedicarboxylic acid as the organic linker, three novel trimetallic metal-organic frameworks; ZnCuMnBDC MOF, ZnCdMnBDC MOF, and ZnCrMnBDC MOF were developed in this study using a solvothermal strategy. They have been characterised using various analytical techniques, including FT-IR, ultraviolet/visible diffuse reflectance spectroscopy (UV-DRS), X-ray powder diffraction studies, N2 adsorption–desorption analysis, scanning electron microscopy (SEM) with energy-dispersive spectroscopy (EDS), and X-ray photoelectron spectroscopy (XPS). These MOFs are explored as catalysts for the photocatalytic degradation of Congo Red dye. Moreover, the catalytic activity of the as-prepared catalysts was assessed in terms of the degradation efficiency.Results and DiscussionAmong these MOFs, ZnCrMnBDC MOF exhibited the highest performance, achieving 98.4% degradation of Congo Red, followed by ZnCdMnBDC MOF at 88.0% and ZnCuMnBDC MOF at 85.89% within 30 minutes of irradiation. These findings underscore the potential of MOFs as effective photocatalysts for environmental remediation under visible light, offering a promising avenue for wastewater treatment.ConclusionThese results highlight that MOFs are potentially efficient photocatalysts for environmental remediation in the presence of visible light, providing an effective wastewater treatment method.
Keywords: photocatalyst